The Utilization of Artificial Intelligence in Decision-Making and Its Effect on Organizational Advancement - Dr. Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study utilizes a quantitative approach to examine the influence of decision-making (X1) and the understanding of artificial intelligence (AI) theory (X2) in organizational development (X3). Data acquired from surveys and documents were analyzed using the Partial Least Squares (PLS) approach, and SmartPLS software was used for hypothesis testing. The data suggest that decision-making has a very favorable impact on the development of organizations, but understanding AI theory has a very negative impact. This research emphasizes techniques for improving the deployment of artificial intelligence in order to promote the growth of organizations by incorporating quantitative analysis, ethical issues, and Industry 4.0 technology.